Development of crop production in the Slovakia and Czechia after the year 2004 in comparison with V4 countries - Némethová Jana; Svobodová Hana; Křejčí Ondřej; Věžník Antonín (Bulletin of Geography. Socio-Economic Series)
The V4 countries went through a transformation of their entire economies, including the agricultural sector, in the 1990s. Each of these countries approached the transformation of agriculture differently, but later the V4 countries’ approach to agricultural development was unified by the EU's common agricultural policy. The aim of the paper was to compare the development of the production (sown area and hectare yield) of selected most commonly cultivated crops in Slovak and Czech regions (NUTS 3) in the period between 2004 and 2017. The development of production in these two countries was also evaluated against the trends of V4 countries. Based on these analyses, common and specific agriculture development trends in V4 countries were revealed. A chronological average was used to evaluate the average values of the monitored indicators in the period from 2004 to 2017 in Slovak and Czech regions. To express the development of the given indicators between 2004 and 2017, the change index was used and visualised cartographically. Regression analysis was used to show the development trends of agricultural production in the V4 countries. In general, the agricultural sectors in the V4 countries show similar characteristics with similar trends, and the average hectare yield has a modest growing trend. In terms of the structure of the cultivated plants, the size of the cultivated areas, the volume of production and the average hectare yields, there have been considerable changes to crop farming in Slovak and Czech regions. The study showed that the changes in the agrarian sector after the year 2004 conditioned by the entry of Czechia and Slovakia into the European Union were reflected in a decrease in crop production and an increase in regional disparities. From the point of view of the production indicator expressing the hectare yield of crops, Czechia achieves better indicator values than does Slovakia.